1976
DOI: 10.1007/bf00423285
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes during exercise testing of patients with ischaemic heart disease

Abstract: Nineteen patients who had recovered from a mild to moderately severe myocardial infraction 6--18 months previously were studied in order to investigate the relationship between the severity of myocardial insufficiency and metabolic changes developing during and after exercise. The patients were compared with six controls by means of a graded exercise test on a treadmill. Electrocardiographic records were made and blood pressure measured during and after the exercise and venous blood samples were taken for meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, with GXT m , AT was lower in dysfunctional mice; a finding similar to those from human research looking at AT in patients with cardiac disease above functional class I (S5 Text, [ 90 ]). Together, these results demonstrated that the GXT m , like the GXT h [ 4 , 72 , 74 , 89 , 91 ], was able to simultaneously elicit exhaustive efforts, true VO 2max , and shift to anaerobic metabolism [ 4 , 72 , 74 , 89 , 91 ].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, with GXT m , AT was lower in dysfunctional mice; a finding similar to those from human research looking at AT in patients with cardiac disease above functional class I (S5 Text, [ 90 ]). Together, these results demonstrated that the GXT m , like the GXT h [ 4 , 72 , 74 , 89 , 91 ], was able to simultaneously elicit exhaustive efforts, true VO 2max , and shift to anaerobic metabolism [ 4 , 72 , 74 , 89 , 91 ].…”
Section: Resultsmentioning
confidence: 85%
“…With the GXT m , Casq2 -/- mice had significantly greater LA delta compared to WT; however, with the PXT m, this parameter was decreased compared to controls ( Fig 4B , S9 Table). In humans with myocardial ischemia, a hallmark response to a GXT h is a significant increase in circulating blood LA concentrations compared to healthy subjects [ 89 ]. Thus, this response was replicated with the GXT m in the genetic model of cardiac insufficiency (9.32 ±1.53mmol/L, Casq2 -/- v. 6.63 ±17mmol/L; WT; Student’s t-Test, alpha = .05; Fig 4B , S9 Table).…”
Section: Resultsmentioning
confidence: 99%